Effect of dietary supplementation and endoparasitic control on the reproductive and productive performance of Menz-type sheep - Ezaz, Z.; Kasali, O.B.; Little, D.A.; Mukasa-Mugerwa, E.; Brokken, R.F.; Akalework, N. (International Livestock Centre for Africa, 1988)
Discusses the progress of a research project underway at Debre Berhan ILCA station carried out to study the effect of dietary supplementation and endo-parasitic control on the reproductive and productive performance of Menz-type sheep.